ANALISIS KARAKTERISTIK GAYA BELAJAR VISUAL, AUDITORIAL DAN KINESTETIK REMAJA DI AMANUBAN BARAT KABUPATEN TIMOR TENGAH SELATAN - Makleat, Nirwaning; Makleat, Melifera Y. (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Style learnedding to constitute combine of someone way in absorbs information, then managing and mengolah is that information as wherewith. Learned style consisting of 3 which is visual's studying style, auditorial, and kinestetik. This research intent for analisis characteristic inspires to study visual, auditorial, and kinestetik. This research is done on 81 students braze VII SMP Country 2 Amanuban West with utilizing kualitatif's approaching descriptive. Data collecting tech that is utilized namely field research, questionnaire broadcast, observation, interview, and field note result. analisis's tech data that is utilized which is utilize analisis's tech Miles And Huberman's model data which is data reduction, data display and conclusion pull. Result observationaling to point out SMP'S student style Country 2 Amanuban West has three type inspire to study which is visual, auditorial, and kinestetik and the most studying style dominant being utilized is styled learned visual. So gets to be concluded that student brazes VII SMP Country 2 Amanuban West more dominant utilize visual's studying style